The effect of knowledge management on improving organizational performance: ( دراسة حالة القطاع الصحي ولاية كسلا في العام 2022م) - د . احمد عبد الرحمن عمر (White Nile Journal for Studies and Research, 2023)
The study aimed to find out the relationship between knowledge management and organizational performance.in the health sector, by studying the health sector in Kassala State in the year 2022 AD. The study was based on the following basic hypothesis: There is a statistically significant relationship between knowledge management and organizational performance.in health sector institutions in Kassala State. The study reached many results, the most important of which are: Knowledge management has a clear impact on organizational performance.in health sector institutions in Kassala State. The study recommended recommendations, the most important of which are: the need to pay attention to knowledge management in its various dimensions in the health sector in order to improve organizational performance.and take the right decisions. Key words: Knowledge management, organizational performance.